A Survey of the Practice Status Quo of Ultrasound-Guided ECC Tip Location for Neonatal Patients in 31 Provinces of China - Xuexiu Liu; Xiaojun Tao; Ye Xu; Xianhong Zhang; Liping Wu (Frontiers in Pediatrics, 2022)
ObjectiveTo investigate the status quo of implementing ultrasound (US)-guided epicutaneo-caval catheters (ECC) tip location for neonatal patients in 31 provinces.MethodsThe convenience sampling method was used to investigate the nursing managers and ECC (or intravenous therapy) nurses of 91 hospitals in 31 provinces from October 29 to November 10, 2021.ResultsThe survey involved a total of 182 medical staff, including 91 managers and 91 nurses, and 91 institutions, including 22 children's hospitals, 49 general hospitals and 21 maternal and child health care hospitals. Sixteen hospitals (17.6%) carried out US-guided ECC for neonatal patients; 176 subjects (96.7%) of the 91 hospitals had known about or heard of the technology of US-guided ECC. The low awareness of operators of the tip location of ECC catheters in children under ultrasound guidance (OR = 2.690, 95% CI = 1.163–6.221), limited conditions in existing wards (OR = 2.953, 95% CI = 1.285–6.790), and insufficient funds (OR = 2.836, 95% CI = 1.149–7.004) were the independent risk factors responsible for the failure to carry out ultrasonic-guided location of ECC tips in newborns.ConclusionThe popularity of neonatal US-guided ECC location was seriously hindered by factors such as a low awareness rate of the project, the low qualification certification rate of the nursing staff, a flawed performance allocation system, and the lack of a professional team, among other factors.